Henni Alftan - Othman, Charlotte; Pinteaux, Baptiste (Galerie Claire Gastaud, 2019)
This first monograph on the Franco-Finnish painter Henni Alftan brings together a wide selection of her latest works. They are introduced by the texts of Julie Crenn & Marja-Terttu Kivirinta, which describe her work in the field of contemporary painting and highlight her interest in the gaze, the double, cinematic composition, and the disquiet aroused by a vision grown so sharp it becomes too precise
Texts by Julie Crenn and Marja-Terttu Kivirinta
Keywords: Alftan, Henni -- 1979-; Alftan, Henni / Expositions; Bildband